Statistical and numerical techniques in the optimization of membrane fabrication variables - Jacobs, E. P.(Edmund Petrus),1951- (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1988.